Serum metabolomics combined with 16S rRNA sequencing to reveal the effects of Lycium barbarum polysaccharide on host metabolism and gut microbiota. (March 2023) - Liang, Jingjing; Li, Xiaohan; Lei, Wenzhi; Tan, Pei; Han, Mengzhen; Li, Hongcai; Yue, Tianli; Wang, Zhouli; Gao, Zhenpeng
Graphical abstract: Highlights: Lycium barbarum polysaccharide (LBP) supports the growth of Lactobacillus . LBP has the potential to prevent hyperlipidemia and nonalcoholic fatty liver disease. LBP intervention significantly changed serum metabolic profiles. Hepatic mRNAs involved in fatty acid oxidation were regulated by LBP. Abstract: Gut microbes and microbial metabolites derived from polysaccharides mediate beneficial effects related to polysaccharides consumption. Lycium barbarum polysaccharide (LBP) is the main bioactive components in L. barbarum fruits and possesses considerable health-promoting effects. In the present study, we aimed to investigate whether LBP supplementation influenced host metabolic responses and gut microbiota in healthy mice, and to identify bacterial taxa associated with the observed beneficial effects. Our results indicated that mice supplied with LBP at 200 mg/kg BW showed lower serum total cholesterol (TC), triglyceride (TG), and liver TG levels. LBP supplementation strengthened the antioxidant capacity of liver, supported the growth of Lactobacillus and Lactococcus, and stimulated short-chain fatty acids (SCFAs) production. Serum metabolomic analysis revealed that fatty acid degradation pathways were enriched, and RT-PCR further confirmed that LBP up-regulated the expression of liver genes involved in fatty acid oxidation. The Spearman's correlation analysis indicated that some serum and liver lipid profiles and hepatic SOD activity were associated with Lactobacillus, Lactococcus, Ruminococcus, Allobaculum and AF12 . Collectively, these findings provide new evidence for the potential preventive effect of LBP consumption on hyperlipidemia and nonalcoholic fatty liver disease.